Echogenicity Changes in Brainstem Raphe Detected by Transcranial Parenchymal Sonography and Clinical Characteristics in Parkinson's Disease - Bei, Hong-Zhe; Chen, Ju-Ping; Mao, Cheng-Jie; Zhang, Ying-Chun; Chen, Jing; Du, Qiao-Qiao; Xue, Fei; He, Pei-Cheng; Jin, Hong; Wang, Fu-Yu; Liu, Chun-Feng (Frontiers in Neurology, 2020)
Background: Decreased brainstem raphe (BR) echogenicity detected by transcranial parenchymal sonography (TCS) is associated with depression in psychiatric and neurologic diseases. However, previous studies focusing on the relationship between motor and non-motor symptoms and echogenicity changes in BR in patients with PD yielded controversial results. Objectives: To investigate the relationship between echogenicity changes in BR detected by TCS and motor and a series of non-motor symptoms in patients with PD. Methods: Consecutive PD patients were recruited from the Second Affiliated Hospital of Soochow University. Demographic information and Motor and non-motor symptoms for all subjects were collected. TCS was used to detect the echogenicity changes in BR in PD patients. Results: One hundred and thirty-five consecutive patients with PD were enrolled in the study. The BR abnormal rate was significantly higher in PD patients with anxiety (p = 0.003) or depression (p = 0.022) than patients without. Spearman correlation analyses showed that Hamilton Rating Scale for Depression(HRSD) (r = 0.274, p = 0.002) and Parkinson's Disease Questionnaire 39-item(PDQ-39) (r = 0.208, p = 0.034) scores were positively correlated with abnormal BR echogenicity. Multivariate logistic regression analyses showed that HRSD and HAMA scores were associated with BR hypoechogenicity, the corresponding odds ratios (confidence intervals) were 1.07 (95% CI, 1.01–1.13) and 1.10(1.01–1.18), respectively. However, the PDQ-39 score was not associated with BR hypoechogenicity. Conclusion: The abnormal reduction in BR echogenicity detected by TCS is associated with depression and anxiety, but not motor symptoms in PD patients.